PENGEMBANGAN SUMBER DAYA MANUSIA SANTRI DI PESANTREN UNTUK MEMASUKI KEHIDUPAN MASYARAKAT ( Studi Pada Pesantren Mahasiswa Al Hikam Malang) - M. Miftahusyaian (lp2m-uin malang, 2007)
Pesantren, recently, is one of educational institutions that still exist in Indonesia’s education. The important role of pesantren in developing human resource is by implementing fighting spirit to its santri2. This study is a descriptive research designed using case study model with the source determined purposively (purposive sampling), by choosing samples who knows the problems, have the data and willing to give the data. The data collection technique is using in depth interview with key informant and document analysis. The data analysis is using data reduction procedure, data presentation, and conclusion/verification making. Data validating is using method and source triangulation. This research objectives are to know deeper about 1) the form of ritual tradition applied in College Student Pesantren Al Hikam and the meaning of the ritual tradition, 2) the strategy of santri’s human resource development in College Student Pesantren Al Hikam in entering the societal life, and 3) the motivation model applied in College Student Pesantren Al Hikam.Keyword: Human Resource, Pesantren, Santri